Inovasi dan Masa Depan Pembiayaan Pendidikan : Menuju Akses dan Kualitas yang Merata - Bagas Prakosa; Siswi Yulfani; Retno Sasti Intan Pangastuti; Qomaruddin Rizal; Siti Aqidatun; Sisca Septiani; Wiwik Pudjaningsih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This article discusses innovative models in higher education financing that aim to expand access and maintain quality more evenly in Indonesia. The main focus of this study is on the challenges of financing higher education, such as limited funds, infrastructure inequality, and quality gaps between regions that are still obstacles to realizing inclusive and quality education. This study uses a qualitative approach with the systematic literature review method on 25 sources of scientific literature published between 2020–2025. The results of the study show that financing models such as public-private partnerships (PPP), education crowdfunding, the use of financial technology (fintech), and Corporate Social Responsibility (CSR) programs have great potential to encourage sustainability and equitable access to higher education. The PPP model, for example, can strengthen synergy between the government and the private sector in the provision of educational infrastructure, while crowdfunding plays a role in opening up wider public participation in supporting student financing. The use of fintech can provide a more flexible, transparent, and accessible payment system, while CSR encourages corporate contributions to support scholarships and university quality development programs. However, its implementation in Indonesia still faces a number of obstacles. Inhibiting factors include limited regulations governing alternative financing, low digital and financial literacy among students and the community, and unevenness in digital infrastructure between regions. Therefore, the development of the higher education financing system in Indonesia needs to be directed at diversifying funding sources, increasing the management capacity of educational institutions, and improving governance to be more accountable and transparent.